2003
DOI: 10.7863/jum.2003.22.8.777
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Wall Thickness on Ultrasonographic Cystourethrography

Abstract: Demographic, anatomic, and urodynamic factors may affect the bladder wall thickness at the trigone, dome, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 17 publications
1
34
1
Order By: Relevance
“…Target structure of the toxin is the detrusor muscle, as its main mechanism of action is at the neuromuscular junction [10,11]. However, detrusor thickness is variable and depends on several factors such as gender, age, bladder filling volume and the presence of neurogenic lesion or obstruction [12,13]. Although injection is performed under cystoscopic guidance, injection depth can only be estimated by the surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…Target structure of the toxin is the detrusor muscle, as its main mechanism of action is at the neuromuscular junction [10,11]. However, detrusor thickness is variable and depends on several factors such as gender, age, bladder filling volume and the presence of neurogenic lesion or obstruction [12,13]. Although injection is performed under cystoscopic guidance, injection depth can only be estimated by the surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the literature evaluating BW thickness at urine volumes up to 250 cm 3 , 12,17 where wall thickness was inversely correlated with urine volume and intravesical pressure. 13,15 This suggests that, for the purposes of generating a BW structure for DVH calculations and dose reconstruction, it would be inaccurate to apply a generic uniform contraction (such as 2.5 mm) to a group of patients. Furthermore, it would also be inaccurate to apply a constant, but patient-specific contraction in multiple images when bladder filling is variable.…”
Section: Discussionmentioning
confidence: 99%
“…However, large variations in BW thickness between patients have been noted, 12,13 and wall thickness has also been inversely related to the volume of urine contained within the bladder. [13][14][15][16] The specifics of that inverse relationship seem to vary for different filling volumes however, 12,17,18 and it has been reported that the volume of the wall actually increases slightly with increasing urine volume owing to the increased blood perfusion in the detrusor muscle at larger urine volumes. 9,19 To facilitate dose reconstruction to the hollow BW, the objective of this study was to evaluate the use of a uniform contraction from the OB surface to delineate the IB surface under variable bladder filling conditions employing: a generic contraction (2.5 mm); a constant, patient-specific contraction; a variable contraction based on patient-specific constant wall volume; and a variable contraction based on patient-specific variable wall volume.…”
Section: Introductionmentioning
confidence: 99%
“…The other possible reason is that the renal parenchyma and perihilar adipose tissue surrounding the renal pelvis may act as a barrier against early spread. 23,24 One study reported an overall better prognosis of renal pelvic tumour than ureteral tumour; the authors suggested the protective role of thick renal parenchyma against local tumour spread. 12 Another reason is adjuvant chemotherapy, which is usually undertaken in UUTUC above T2, according to the medical insurance policy in Korea.…”
Section: Cuaj • April 2013 • Volume 7 Issues 3-4 E218mentioning
confidence: 99%